Hybrid weighted communication network node importance evaluation method - Tian, Gan; Yang, Xinzhi; Li, Yaxiong; Yang, Zhengwei; Chen, Gong (Frontiers in Physics, 2023)
Communication networks are used as an important guarantee for information interaction and efficient collaboration within many fields and systems; however, under information technology conditions, the destruction of a few nodes in the network may have a great impact on the overall operation of the network. Therefore, it is important to accurately discover the critical nodes in the network to enhance the network resistance to destruction. Combining the characteristic attributes of the communication network, the node contribution evaluation matrix (CEM) is proposed based on the efficiency matrix from the perspective of node receiving information; the node value evaluation matrix (VEM) is proposed from the perspective of node providing information to neighboring nodes, and the node importance is calculated by integrating the evaluation results of the two matrices and the node's own attributes. The algorithm is suitable for directed-weighted network node value evaluation, and the effectiveness and accuracy of the algorithm are verified by comparing other algorithms in a small-scale network. In further experimental validation, a hybrid weighted communication network evolution model based on organizational structured networks (OSN) is proposed, and networks of different sizes are generated for experimental simulation. The results show that when nodes with high importance are removed from the network, they can cause a rapid decrease in network efficiency and maximum connectivity, confirming the accuracy of the algorithm in evaluating the importance of nodes and identifying critical nodes in the network.